2017
DOI: 10.1038/s41598-017-15816-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity and Population Structure in Iranian Cannabis Germplasm

Abstract: Cannabis sativa has a complex history reflected in both selection on naturally occurring compounds and historical trade routes among humans. Iran is a rich resource of natural populationswhich hold the promise to characterize historical patterns of population structure and genetic diversity within Cannabis. Recent advances in high-throughput DNA sequencing technologies have dramatically increased our ability to produce information to the point that it is now feasible to inexpensively obtain population level ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 64 publications
8
63
1
Order By: Relevance
“…This difference may be because all the progeny from our three crosses are half-siblings. Withinpopulation variation was greater than amongpopulation variation for C. sativa germplasm from Iran and Afghanistan (Soorni et al, 2017), and hemp accessions from Europe and Asia (Sawler et al, 2015). Small (2015) reported that selfing in cannabis induces inbreeding depression.…”
Section: Resultsmentioning
confidence: 99%
“…This difference may be because all the progeny from our three crosses are half-siblings. Withinpopulation variation was greater than amongpopulation variation for C. sativa germplasm from Iran and Afghanistan (Soorni et al, 2017), and hemp accessions from Europe and Asia (Sawler et al, 2015). Small (2015) reported that selfing in cannabis induces inbreeding depression.…”
Section: Resultsmentioning
confidence: 99%
“…sativa indica , and ruderalis has been hotly debated but infrequently verified with genomic surveys. Segregation of fiber-based cannabis (hemp) and drug type cannabis (sometimes referred to as marijuana) has been genetically resolved (Small; Hillig and Mahlberg 2004; Fischedick et al 2010; van Bakel et al 2011; Hazekamp and Fischedick 2012; Sawler et al 2015; Ryan C. Lynch 2016; Soorni et al 2017). Hemp genetics are ancestral and often produce distinct male and female flowers on a single plant (monoecious).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this fact, there has been an increased interest in recent years of the potential use of cannabis derivatives in medical applications [ 65 ]. In this regard, reviewing and rewriting the regulations by governments, introducing novel gene pools of dwarf and low THC/high CBD accessions, and the development of techniques to accurately characterize the chemical phenotypes (drug and nondrug cannabis plants) have made a significant contribution to the acceptance of this issue and the control of legal and illegal cannabis cultivation [ 6 , 68 ].…”
Section: Phytocannabinoidsmentioning
confidence: 99%
“…Cannabis is both a medicinal and industrial plant native to Central Asia. It has been globally used for thousands of years as a source of food, feed, fuel, fiber, medicine, and narcotics [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%